Processing of cranberry chutney and gluten-free biscotti - Savage, Sierra; Mills, McKenna; Herl, Bethany; Alexander, Hannah; Getty, Kelly J.K. (My University, 2017)
The cranberry is known as the “king” of wholesome fruits. Consumer health trends have focused on clean labels and minimally processed foods. The objective of this project was to provide consumers with a healthy, on-the-go product using frozen whole cranberries. The main goal was to develop a minimally processed cranberry chutney, along with the gluten-free biscotti that provided a convenient, light, and tasty product for “healthy strivers.” A shelf stable cranberry chutney and gluten-free biscotti was the desired product. Several processing methods and formulations were conducted for each component. A combination of whole cranberry, pears, apple, pineapple, Anaheim pepper, cilantro, and ginger were evaluated at different levels to determine the appropriate sweetness and heat profile of the chutney. Ingredients were diced and/or pulverized to provide a uniform consistency. The chutney was cooked to an internal temperature of 160°F for 60 seconds before being placed in glass jars to conduct an accelerated shelf stability test. Water activity and pH were measured. Different functional ingredients such as xanthan gum and eggs were added to the biscotti to obtain a uniform product. A focus group was conducted. After many trials, the best formulation and processing steps were developed. Ingredients in the chutney were 30.7% cranberry, 26.3% pear, 13.8% apple, 12.1% pineapple, 12.1% sugar, 2.85% Anaheim pepper, 1.1% cilantro, and 1.1% ginger. For the chutney, it was found that pulverizing 50% of the pear, and 100% of the cranberry, Anaheim pepper, cilantro, and ginger provided a smooth, uniform texture. The remaining pear and 100% of the apple were diced to a size of 0.5 cm × 0.25 cm to provide an appealing product with crunchy notes. Crushed, canned pineapple was drained and added to the chutney mixture to provide a sweet, fruity flavor. The gluten-free biscotti had 15.4% cranberry. The shelf stability of the cranberry chutney was found to be at least one year. The time could increase with a higher cooking temperature or longer holding time. The pH consistently stayed at 2.99. Water activity of the cranberry chutney was 0.976. Based on focus group results, the chutney scored favorably above the biscotti. The cranberry chutney will provide a unique “sweet and heat” minimally processed product to “healthy strivers.
Keywords: Spring 2017